DOCK8 DEFICIENCY AND A DIAGNOSTIC SCORE TO DIFFERENTIATE IT FROM OTHER HYPER-IGE SYNDROMES - Engelhardt, K. R.; Gertz, E. M.; Keles, S.; Schaeffer, A. A.; Ceja, R.; Sassi, A.; Grimbacher, B. (Springer/Plenum Publishers, 2012)
[Abstract Not Available]
15th Biennial Meeting European-Society-for-Immunodeficiency (ESID) -- OCT 03-06, 2012 -- Florence, ITALY